Predicting thermal performance of a mass concrete foundation – A field monitoring case study. (December 2019) - Sargam, Yogiraj; Faytarouni, Mahmoud; Riding, Kyle; Wang, Kejin; Jahren, Charles; Shen, Jay
Highlights: Early-age temperature development of a bridge foundation was monitored and predicted. A computer program, ConcreteWorks, was used for concrete temperature prediction. Concrete temperature is sensitive to changes in materials, mix design and construction. ConcreteWorks can be used to optimize mix proportion and develop a thermal control plan. Abstract: High-temperature differentials in a mass concrete structure pose great risks of temperature-induced stresses and cracking. Prior knowledge of temperature development within such a structure is essential. In this context, this paper presents a case study in which the construction of a mass concrete bridge foundation in Iowa, USA was investigated and a computer program, ConcreteWorks (CW), was used to predict its overall thermal performance with an aim to prevent thermal cracking. The properties of mass concrete mixes, required as CW inputs, were measured through isothermal and semi-adiabatic calorimetry tests. The temperature development profile, temperature differential, maturity, and compressive strength of the mixes were predicted and compared with those measured through the real-time monitoring of the bridge foundation. It was observed that CW predictions match well with their corresponding measured values. Three locations, core, top, and the face nearest to the core of the foundation, were found to be critical points for high temperature differentials. A sensitivity analysis, analyzing the effects of various mass concrete parameters, is also presented. The results provided clear insights into the temperature development of concrete with complex material compositions and environmental conditions. CW is a useful tool in developing thermal control plan for mass concrete projects.